Design and Measurement Properties of the Online Gambling Disorder Questionnaire (OGD-Q) in Spanish Adolescents - González-Cabrera, Joaquín; Machimbarrena, Juan Manuel; Beranuy-Fargues, Marta; Pérez-Rodríguez, Priscila; Fernández-González, Liria; Calvete, Esther (Journal of Clinical Medicine, 2020)
Gambling disorder is of great clinical and social relevance since it seriously affects people who suffer from it. More recently, the Internet has exacerbated the problem with online casinos, poker, and sports betting. However, there is little evidence of this problem, and we know of no diagnostic questionnaire. The main objectives of this study were to develop the Online Gambling Disorder Questionnaire (OGD-Q) for adolescents, evaluate its main psychometric properties, and establish diagnostic criteria to differentiate pathological from non-pathological online gamblers. We conducted a study in 16 schools across seven regions of Spain, sampling 2691 adolescents, 883 of whom had reported some online gambling experience. Of those, 602 were boys (68.2%) and 281 were girls (31.8%) Sampling was non-probabilistic and incidental. Mean age and standard deviation were 14.25 +/- 1.55 (11-19 years). Confirmatory factor analysis yielded a one-dimensional model with a good fit. The reliability indicators were satisfactory (>0.94). The scores on the OGD-Q were related to other constructs, such as Internet gaming disorder, problematic Internet use, and nomophobia. Participants classified as having problems or being at risk of online gambling disorder presented significantly more stress, anxiety, and depression. Participants categorized as having online gambling disorder comprised 0.89% (n = 24) of the total sample and 2.71% of those who have gambled at some time. We discuss these findings and their practical implications in this article and propose future lines of research.
Keywords: online gambling disorder; pathological online gambling; Internet; adolescents; questionnaire; validation; JCR; Scopus